Pseudo-transformational Leadership is in the Eyes of the Subordinates - Lin, Chiou-Shiu (Journal of business ethics, 2017)
Based on attribution theory, this research defines pseudo-transformational leadership to be driven by the interaction between transformational leadership and the subordinates’ perception of their supervisor’s manipulative intention. We investigate the effects of pseudo-transformational leadership on contextual performance through organizational identification. The results of hierarchical linear modeling using a sample of 214 subordinates reporting to 66 supervisors show that when subordinates perceive that their supervisor has a high level of manipulative intention, the impact of group-level transformational leadership on the subordinates will be reduced. More specifically, when subordinates perceive the manipulative intention of transformational leadership, they are less likely to identify with the organization, which ultimately limits their willingness to demonstrate contextual performance activities. The implications of these findings for theory as well as managerial practice are discussed.